Posters and Development: A Case Study of Cell Phone Posters in the Rural Congo - Sylvain Cibangu (Journal of Social and Development Sciences, 2022)
One of the benchmarks of the information age often forgotten is the proliferation of posters or billboards in and around workplaces, neighborhoods, airports, shopping centers, restaurants, theaters, libraries, schools, etc. More interestingly, through cell phones, posters are rapidly entering rural areas in developing countries. Although these posters come with specific messages and graphics – continually upgraded and tailored to people’s attention -- they hardly undergo scientific inquiry in circles concerned with information and communication technologies [ICTs]. The lack of attention raises questions on the role of information systems and related wireless devices being deployed in developing countries. The present paper aimed to canvass cell phone posters and unbundle the underlying practices and routines. As well as positioning posters at the center stage of ICT research, the present paper applied critical discourse analysis to inquire into ways in which development was represented or effected among populations in the rural Congo.The paper determined that posters were not centered on local populations and their day-to-day struggles/needs, and that the information conveyed on posters was not geared toward the development of the world’s poorest. The paper crafted some paths for future work in ICT fields and cell phone bodies of work.